Olfactory assessment using the NIH Toolbox - Dalton, Pamela (Lippincott Williams & Wilkins, 2013)
The human olfactory system provides us with information about our environment that is critical to our physical and psychological well-being. Individuals can vary widely in their ability to detect, recognize, and identify odors, but still be within the range of normal function. Although several standardized tests of odor identification are available, few specifically address the issues in testing very young children, most of whom are likely to be unfamiliar with many of the odor stimuli used in adult tests and have limited ability to read and identify labels to select among choices. Based on the format of the San Diego Odor Identification Test and the delivery system of the University of Pennsylvania Smell Identification Test, we developed 2 versions of an odor identification test using standardized odor stimuli in a scratch-and-sniff format in which participants match 5 (children) or 9 (adults) odors to pictures representing the odor source. Results from normative testing and validation showed that for most participants, the test could be completed in 5 minutes or less and that the poorer performance among the youngest children and the elderly was consistent with data from tests with larger numbers of items. Expanding on the pediatric version of the test with adult-specific and public health–relevant odors increased the ecological validity of the test and facilitated comparisons of intraindividual performance across developmental stages.